The Impact of a 24-h Ultra-Marathon on Circulatory Endotoxin and Cytokine Profile - Gill, S. K.; Hankey, J.; Wright, A.; Marczak, S.; Hemming, K.; Allerton, D. M.; Ansley-Robson, P.; Costa, R. J. S. (International Journal of Sports Medicine, 2015)
The study aimed to determine circulatory endotoxin concentration, cytokine profile, and gastrointestinal symptoms of ultra-endurance runners (UER, n=17) in response to a 24-h continuous ultra-marathon competition (total distance range: 122–208 km) conducted in temperate ambient conditions (0–20°C) in mountainous terrain. Body mass and body temperature were measured, and venous blood samples were taken before and immediately after competition. Samples were analysed for gram-negative bacterial endotoxin, C-reactive protein, cytokine profile, and plasma osmolality. Gastrointestinal symptoms were also monitored throughout competition. Mean exercise-induced body mass loss was (mean±SD) 1.7±1.8% in UER. Pre- and post-competition plasma osmolality in UER was 286±11 mOsmol·kg−1 and 286±9 mOsmol·kg−1, respectively. Pre- to post-competition increases (p<0.05) were observed for endotoxin (37%), C-reactive protein (2 832%), IL-6 (3 436%), IL-1β (332%), TNF-α (35%), IL-10 (511%), and IL-8 (239%) concentrations in UER, with no change in the control group (CON; n=12) observed (p>0.05). Gastrointestinal symptoms were reported by 75% of UER, with no symptoms reported by CON. IL-10 (r=0.535) and IL-8 (r=0.503) were positively correlated with gastrointestinal symptoms. A 24-h continuous ultra-marathon competition in temperate ambient conditions resulted in a circulatory endotoxaemia and pro-inflammatory cytokinaemia, counteracted by a compensatory anti-inflammatory response.
Keywords: inflammatory; cytokinaemia; endotoxaemia; sleep deprivation; energy balance; physical exertion